ANALISIS PENGARUH HARGA, PELAYANAN, LOKASI DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Minimarket Alkhaibar) - Fauziyah Irfan; Agus Widarko; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis study aims to: a) know and analyzepartial of price (x1) service (x2) location (x3) and product diversity (x4) on purchase buying decision (Y) in Alkhaibar minimarket. b) to know and analyze the effect of  simultaneous price, service, location and product diversity in Alkhaibar minimarket. this researchs explanatory researchs with quantitave approach. The data source of this research is the spread of a list of questions (questionnaire) to consumers Alkhaibar minimarket. The data used is primary and secondary. This  analyze uses SPSS data. This results in tis research showed that price, service, location and product diversity purchases buying decision. Key word- price, service, location and product diversity